Ekonomi kreatif dan transformasi digital: Sinergi yang mengubah dunia bisnis - Ainurrohmah, Cindy (Maliki Interdisciplinary Journal, 2024)
This study aims to creative economy and digital transformation can synergize to transform the business world that can increase the competitiveness of local products in the global market. Digital transformation and creative economy drive economic growth and the competitiveness of local products in the global market. The Indonesian government has made digital transformation a priority to improve the country's economy, especially in the creative economy. Businesses must use digital technology to remain competitive and relevant in today's digital era. Indonesia has taken steps to utilize digital transformation in the creative sector that has the potential to significantly accelerate the growth of the creative economy. Based on the results of the study, it is known that an alternative approach to achieving sustainable economic development is known as the "creative economy," which aims to achieve growth through innovation, originality, and imagination. Digital transformation brings major changes to Indonesian business and economy, increasing company revenues and creating competitive advantages. However, the adoption of technology is constrained by issues of data security, regulation, and lack of control. Developing human resource skills is essential to face future challenges. Companies need to invest in technology and human resource skills.